On ten jumping spider species described by Song and Chai (1992) based on type specimens (Araneae, Salticidae) - Lin, Yejie; Xin, Yafei; Wang, Cheng; Li, Shuqiang (Zootaxa, 2023)
Ten jumping spider species published by Song and Chai in 1992 are restudied. The following new synonyms are proposed: Chinattus emeiensis (Peng & Xie, 1995) syn. nov. [=C. undulatus (Song & Chai, 1992)], Evarcha paralbaria Song & Chai, 1992 syn. nov. (= E. coreana Seo, 1988), Ptocasius nanyuensis (Xie & Peng, 1995) syn. nov. [=P. badongensis (Song & Chai, 1992)]. Evarcha orientalis (Song & Chai, 1992) is transferred to Nigorella Wesołowska & Tomasiewicz, 2008. The synonymy status of Chinattus szechwanensis (Prószyński, 1992) with C. undulatus (Song & Chai, 1992) and Nigorella hunanensis (Peng, Xie & Kim, 1993) with N. hirticeps (Song & Chai, 1992) are restored.